1991
DOI: 10.1203/00006450-199106010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Number and Binding Affinity in Newborn Dogs

Abstract: The insulin resistance in newborn mammals may be caused by a receptor or postreceptor defect. Although liver and umbilical cord blood monocytes have increased numbers of insulin receptors, there is a paucity of information about other neonatal tissues. Glucose disposal takes place primarily in the skeletal muscle; therefore, it is important to evaluate this tissue for an insulin receptor defect. To determine the role of insulin receptors in neonatal insulin resistance, neonatal and adult canine skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The detection of two insulin binding sites in canine muscle is in agreement with insulin binding data previously described for dogs by Johnston et al (1991). It was proposed that binding of insulin to the S1 of one α-monomer is followed by cross-linking of insulin to the S2' of the alternate α-monomer, with resultant S1/S2' high-affinity binding.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The detection of two insulin binding sites in canine muscle is in agreement with insulin binding data previously described for dogs by Johnston et al (1991). It was proposed that binding of insulin to the S1 of one α-monomer is followed by cross-linking of insulin to the S2' of the alternate α-monomer, with resultant S1/S2' high-affinity binding.…”
Section: Discussionsupporting
confidence: 76%
“…These changes in insulin bin- I-insulin bound (y axis), so the further to the right the curve is, the greater the insulin resistance. These data were inserted in the Ligand sub-directory of Kell for Windows TM version 6 (Biosoft) to generate Kd and Bmax values for both insulin binding sites shown in Table 2. ding characteristics were detected only at the high-affinity binding sites, and it seems that in dogs, low-affinity binding sites are less susceptible to modulation, once Johnston et al (1991), after studying insulin binding properties in different tissues of adult and newborn dogs, also found changes only at high-affinity binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that the insulin receptor concentration in skeletal muscle was twofold higher in 7-than in 26-day-old pigs. Studies have shown that insulin receptor abundance in muscle is also higher in suckling than in adult rats and dogs (1,29). However, in those studies, age-related changes in insulin receptor abundance were confounded by changes in diet composition.…”
Section: Effect Of Development On Insulin Receptor Irs-1 and Irs-2 mentioning
confidence: 99%